INVESTIGATING PONDING DEPTH AND SOIL DETACHABILITY FOR A MECHANISTIC EROSION MODEL USING A SIMPLE EXPERIMENT - Gao B.; Walter M.T.; Steenhuis T.S.; Parlange J.Y.; Nakano K.; Rose C.W.; Hogarth W.L. (My University, 2003)
This work extends the simple experimental studies initiated by Heilig et al. [J. Hydrol. 244(2001) 9] to study erosion processes inherent to a mechanistic soil erosion model (the Rose model) that were not addressed in earlier studies. Specifically, we investigated the impacts of ponding water depth and soil detachability on erosion. The Rose model describes the interplay among the processes of soil detachment, transport, deposition, and redetachment, which are involved in rain-induced soil erosion and sediment transport. The simple experiment that was used to improve our understanding of how water-ponding and soil detachability affect soil erosion utilized a small, horizontal, uniform, soil surface exposed to uniform, simulated rainfall. Rainfall rates were systematically changed between 6 and 48 mm h-1. Soil detachability was associated with a clay soil prepared at two different water contents. The Rose model was applied to the experimental conditions and the predicted erosion behavior was compared to experimental measurements. Observed data compared very well with the model results. The experimentally observed relationship between ponding water depth and soil detachability agreed well with previously proposed theories; soil detachability was constant for ponding depths below a critical depth and dramatically decreased above the critical depth. Also, these experiments corroborated that the soil detachability as represented in the Rose model is independent of rain intensity. These results provide support to the validity of the Rose model with respect to the roles of surface water-ponding and its relationship to soil detachability. These mechanisms can be incorporated into models of more complicated and realistic systems in which these individual processes may be difficult to explicitly identify.
Keywords: SOIL EROSION; MECHANISTIC MODEL; SURFACE WATER PONDING; SOIL DETACHABILITY; RAINDROP DETACHMENT